2020
DOI: 10.3389/fimmu.2020.00386
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B Cells Are Decreased and Impaired in Their Function in Peripheral Maternal Blood in Pre-term Birth

Abstract: Preterm birth (PTB) is defined as birth before 37 completed weeks of gestation. The causes of PTB are multiple and complex, the underlying pathophysiology being largely unknown. Interferences in the fine-tuned balance of the maternal immune system have been pointed to as one possible cause of PTB. Regulatory B cells (Breg) are part of the adaptive immune response, and recent data suggest that they may contribute to a healthy pregnancy by their regulatory/suppressive function. We investigated the frequency of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…We also observed B10 expansion during pregnancy in mice and humans [7][8][9]: here, IL-10 helps to hamper the proinflammatory cytokines produced by maternal T cells [8]. The inability to expand this population is associated with fetal rejection in mice [7] and spontaneous abortion or preterm delivery in humans [8,9]. As such, transferring B10 cells or a subpopulation of B1a B cells characterized by high PC1 expression and IL-10 secretion can normalize the otherwise increased spontaneous abortion rate in an experimental mouse model [10].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…We also observed B10 expansion during pregnancy in mice and humans [7][8][9]: here, IL-10 helps to hamper the proinflammatory cytokines produced by maternal T cells [8]. The inability to expand this population is associated with fetal rejection in mice [7] and spontaneous abortion or preterm delivery in humans [8,9]. As such, transferring B10 cells or a subpopulation of B1a B cells characterized by high PC1 expression and IL-10 secretion can normalize the otherwise increased spontaneous abortion rate in an experimental mouse model [10].…”
Section: Introductionsupporting
confidence: 57%
“…Consequently, our follow-up study aimed to understand the signaling mechanisms activated by LPS in maternal B cells and the role in pregnancy complications, particularly in IUFD. We also observed B10 expansion during pregnancy in mice and humans [7][8][9]: here, IL-10 helps to hamper the proinflammatory cytokines produced by maternal T cells [8]. The inability to expand this population is associated with fetal rejection in mice [7] and spontaneous abortion or preterm delivery in humans [8,9].…”
Section: Introductionmentioning
confidence: 61%
“…Increased RANTES and MCP-1 levels were also detected in the serum from CD19 −/− and µMT mice. We previously observed enhanced inflammatory cytokine concentrations in human PTB [ 4 , 5 , 30 ]. Others found this connection also in murine PTB models [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A reduced number of ICOS-expressing peripheral T cells were determined in patients with spontaneous preterm labor, preeclampsia and HELLP syndrome [ 67 , 68 ]. Since we have shown that patients with spontaneous preterm labor, preeclampsia or HELLP syndrome had elevated levels of pro-inflammatory cytokines such as IL-6 and a diminished percentage of IL-10-secreting B cells [ 4 , 5 , 30 ], ICOS-expressing T cells may be involved in the regulation of IL-10-secreting B cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation